DYNAMIC MODEL OF ZETA CONVERTER WITH FULL-STATE FEEDBACK CONTROLLER IMPLEMENTATION - Sarkawi, Hafez; Jali, Mohd Hafiz; Ahmad Izzuddin, Tarmizi (Sun Publications, 2013)
Zeta converter is a fourth order dc-dc converter that can increases (step-up) or decreases (step-down) the input voltage. By considering dynamic model of the converter, the accuracy of the converter’s modeling and simulation are increased thus make it easier to produce the hardware version of the converter. State-space approach is a time-domain method for modeling, analyzing, and designing a wide range of systems which can be described by differential equations or difference equations. This gives great advantages because it particularly suited for digital computer implementation for their time-domain approach and vector-matrix description. The converter needs feedback control to regulate its output voltage. This paper presents the dynamic model of zeta converter. The converter is modeled using state-space averaging (SSA) technique. Full-state feedback controller is implemented on the converter to regulate the output voltage. The simulation results are presented to verify the accuracy of the modeling and the steady-state performance subjected to input and load disturbances.